Terms of Address Preferences and the Role of Chineseness of Two Chinese Surabayanese - Ida Mustika Dewi; Esther Kuntjara (Institute of Research and Community Outreach - Petra Christian University, 2023)
This research is conducted to find out the terms of address preferences and the role of Chineseness of two Chinese Surabayanese. What terms of address do the informants of Chinese Indonesians in Surabaya prefer to be addressed at home? Why do they prefer to be addressed that way? How do their terms of address preferences show their Chineseness as Chinese Indonesians? The research used two informants of Surabayanese Chinese Indonesians, one (male) is from the totok family and the other one (female) is from the peranakan family. Qualitative approach combined with semi-structured and open-ended interview are used. Thematic analysis is used to analyze the findings. The findings show that the family’s background played the important role in the terms of address preferences. The one from totok family still maintained Chinese terms of address, while the one from peranakan family had already abandoned the Chinese terms of address.